Strengthening of RCC Beams in Shear by Using SBR Polymer-Modified Ferrocement Jacketing Technique - Rajinder Ghai; Prem Pal Bansal; Maneek Kumar (Advances in Civil Engineering)
There is a common phenomenon of shear failure in RCC beams, especially in old buildings and bridges. Any possible strengthening of such beams is needed to be explored that could strengthen and make them fit for serviceable conditions. The present research has been made to determine the performance of predamaged beams strengthened with three-layered wire mesh polymer-modified ferrocement (PMF) with 15% styrene-butadiene-rubber latex (SBR) polymer. Forty-eight shear-designed and shear-deficient real-size beams were used in this experimental work. Ultimate shear load-carrying capacity of control beams was found at two different shear-span (a/d) ratios 1 and 3. The sets of remaining beams were loaded with different predetermined damage levels of 45%, 75%, and 95% of the ultimate load values and then strengthened with 20 mm thick PMF. The strengthened beams were then again tested for ultimate load-carrying capacity by conducting the shear load test at a/d = 1 and 3. As a result, the PMF-strengthened beams showed restoration and enhancement of ultimate shear load-carrying capacity by 5.90% to 12.03%. The ductility of strengthened beams was improved, and hence, the corresponding deflections were prolonged. On the other hand, the cracking pattern of PMF-strengthened beams was also improved remarkably.